Influence Of Islamic Ethical Teachings On Civic Responsibility And Social Behaviour Among Secondary School Students In Gusau Metropolis, Zamfara State, Nigeria - Sule Muhammad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examined the influence of Islamic ethical teachings on civic responsibility and social behaviour among secondary school students in Gusau Metropolis, Zamfara State, Nigeria. The research was prompted by increasing moral decline and civic irresponsibility among youths despite formal instruction in Islamic Religious Studies. Anchored on Bandura’s Social Learning Theory, the study adopted a descriptive survey design involving 357 Senior Secondary School Three (SS III) students selected through a multistage sampling procedure from public and private schools. Data were collected using a validated questionnaire titled Islamic Ethical Teachings, Civic Responsibility and Social Behaviour Questionnaire (IETCRSBQ), with a reliability coefficient of 0.91. Descriptive and inferential statistics, including Pearson correlation and independent t-test, were employed for data analysis at a 0.05 significance level. Findings revealed a significant positive relationship between Islamic ethical teachings and students’ civic responsibility and social behaviour. Students exposed to Islamic moral values demonstrated higher levels of discipline, honesty, tolerance, and respect for societal norms. However, the study identified challenges such as inadequate teacher preparation and weak moral supervision in schools. It concluded that the consistent integration of Islamic ethical principles into civic education enhances students’ moral character and civic engagement. The study recommended teacher capacity building, curriculum reinforcement, and the promotion of Islamic moral clubs to foster responsible citizenship and harmonious coexistence among students.